Barriers to Successful Beekeeping: Insights from the Jammu Region of Jammu and Kashmir, India - , Goldy Bhagat; , Anil Bhat; , Jyoti Kachroo; , Rakesh Sharma; , L. K. Sharma; , Manish Sharma (Archives of Current Research International, 2024)
This study focused on the constraints faced by the beekeepers of Jammu region of Jammu and Kashmir, evaluating constraints perceived by the beekeepers identified from Krishi Vigyan Kendras (KVKs) who have been involved in beekeeping for the last five years at least and the list contained eight beekeepers. By using the sampling method with replacement, the sample size of eight beekeepers were interviewed two times and comparison made for three time periods or years viz; 2019-20, 2021-22 and 2023-24, which made the ultimate sample size of twenty four (24) beekeepers. For analyzing the data collected for three time periods, Henry Garrett’s ranking and Chi-square test were used. Findings indicated that major production constraints were the disease of honey bees (78.60), death of the colony (70.00), and heavy rainfall (61.00). Marketing constraints included the fluctuating price of raw honey (69.20), unorganized and unregulated markets (63.20) and lack of government concern or support for the marketing of honey (55.80). Economic constraints featured the huge cost of investment is ranked first with an average score of 71.00, followed by no insurance facilities for the beehives with an average score of 53.67 and lack of credit supply for costly implements used in processing, packaging and quality testing (50.67). Chi-square test revealed that only two constraints under production problems such as, the lack of beehive equipments and materials in the local market (14.77) and pesticide poisoning (7.88) were significant and were showing dependency over the years. By addressing all these constraints through targeted interventions could significantly enhance the viability of beekeeping.